Identification of novel 1,4-dioxane degraders and related genes from activated sludge by taxonomic and functional gene sequence analysis - Chen, Ruihuan; Miao, Yu; Liu, Yun; Zhang, Lan; Zhong, Ming; Adams, Jonathan Miles; Dong, Yuanhua; Mahendra, Shaily (Journal of hazardous materials, 2021)
This study used integrated omics technologies to investigate the potential novel pathways and enzymes for 1,4-dioxane degradation by a consortium enriched from activated sludge of a domestic wastewater treatment plant. An unclassified genus belonging to Xanthobacteraceae increased significantly after magnetic nanoparticle-mediated isolation for 1,4-dioxane degraders. Species with relatively higher abundance (> 0.3%) were identified to present high metabolic activities in the biodegradation process through shotgun sequencing. The functional gene investigations revealed that Xanthobacter sp. 91, Xanthobacter sp. 126, and a Rhizobiales strain carried novel 1,4-dioxane-hydroxylating monooxygenase genes. Xanthobacter sp. 126 contained the genes coding for glycolate oxidase, which was the main enzyme responsible for utilization of 1,4-dioxane intermediates through the TCA cycle, and further proven by the specific glycolate oxidase inhibitor, α-hydroxy-2-pyridinemethanesulfonic acid. An expanded and detailed degradation pathway of 1,4-dioxane was proposed on the basis of the three major intermediates (2-hydroxy-1,4-dioxane, ethylene glycol, and oxalic acid) confirmed by metabolomics. These findings of microbial community and function as well as the novel pathway will be valuable in predicting natural attenuation or reconstruction of a bacterial consortium for enhanced remediation of 1,4-dioxane-contaminated sites as well as wastewater treatment. [Display omitted] •1,4-Dioxane degradation by a complex consortium was studied using integrated omics.•Key dioxane degraders in the consortium belonged to Xanthobacter and Rhizobiales.•YHS and 4-hydroxyphenylacetate 3-hydroxylase enriched in 1,4-dioxane hydroxylation.•1,4-Dioxane biodegradation pathway and enzymes and hosts in consortium was proposed.•The role of etherase in 1,4-dioxane degradation was a novel result in this study.